Investigation of Streptococci in Oral Flora in Terms of Identification in Forensic Sciences - Bozaslan, Buse Sabiha; Çakan, Hüseyin (The Bulletin of Legal Medicine, 2021)
Forensic Microbiology which is a new field and mentioned about this microscobic evidences in forensic science; comes into question in terms of defined of microorganisms with protected innocents and defined guilty at the result of changing social life. Located in mind that study of oral microflora streptococcus that we might be made on various objects; named in identification of microorganisms used and can not be used, planned to investigate. This study; 50 people in the mouth, apples, cigarettes and chewing gum swabs cultivation operation, including 200 different swab broth is made. All of microorganisms that have been investigated in the oral microflora of people. According to the obtained data; as the predominant species in these microorganisms has been determined that alpha hemolytic streptococci. It is unique flora in the mouth of people the rare microorganisms in the mouth that some people are determined to make it special in terms of identification. In this case, the bite mark left in any place, in any event and any objects it has been possible to say that an evidence of the gain will betray that person. As a result; so much in terms of clinical and forensic science is important to us that these bacteria Streptococcus, we aim to contribute with a different approach in terms of forensic microbiology.